The identity of the traditional costume : Japan and Europe - Shirato, Mai, 1978- (2012)
The traditional costume is the symbol of the nationality. We can see many kinds of styles, admirable textiles and fabrics in their costume all around the world. The traditional costume is closely linked to the custom, which has practiced in that area so that the respective dress pattern represents the nation or religion to express who they are. My interest in the traditional costume has begun since I moved to Iceland. I focused on the waistline of both costumes in Iceland and Japan, because there is the great difference between both costumes: the waistline is straight in the kimono as Japanese costume but tightened in the Icelandic costume. During the research for this thesis, I found that the European traditional costume has similar dress pattern and a corset has been used to emphasize women’s bodyline to appeal an ‘hourglass.’ On the other hands, the Japanese kimono conceals women’s bodyline. From my findings, I assume that this difference on both costumes shows the different approach how people and society perceive on dress and women. The ‘hourglass’ is a symbol of femininity in European tradition, but not in Japan. This is to say that the traditional costume is not only the dress to decorate on women’s body, but also to express the identity of their life and culture. In modern times, the traditional costume has inspired into many fashion designers to create new fashion. The waistline of the dress was the important scale to indicate the fashion changes before. However, the term ‘Fashion’ has become wider with globalization so that the discussion on the waistline is no longer the matter to define what the femininity is or not. The purpose of this study is to find the way to analyze the traditional costume in different approaches, comparing features between kimono as a Japanese costume and European costume.